Subungual osteo-cartilaginous exostosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
A 18-year-old girl was first observed due to a subungual lesion of the left hallux. The lesion was painful at palpation but not spontaneously. It had been previously diagnosed as common wart and treated five times with cryotherapy. On physical examination (Fig. 1), there was an about 4 millimeters in size neoformation, with hard consistency, under the medial distal extremity of the nail. The skin overlying the neoformation did not present dermatoglyfics and half-revealed irregular hemorrhages. However, its was smooth and not warty, leading to the diagnosis of osteo-cartilaginous exostosis. X-ray examination (Fig. 3) of the hallux strengthen-ed the clinical suspicion. After the radical surgical removal of the tumor, the clinical suspicion was definitively confirmed by the pathological finding of the neoformation (Fig. 2) showing in the dermis sheets of bone tissue.